(untitled) (American Journal of Pedagogical and Educational Research, 2026)
This article explores the national and genre-specific features of English and Uzbek drama through a comparative analysis of the works of Richard Brinsley Sheridan and Erkin Vohidov. The study examines the distinctive characteristics of both dramatic traditions, focusing on genre structure, conflict, characterization, and artistic style. The analysis reveals both similarities and differences in the representation of social and moral issues, reflecting the cultural and literary traditions of England and Uzbekistan. The findings contribute to a deeper understanding of national literary identities and the development of comparative literary studies.